Study on Squeeze Film Characteristics in Synovial Hip Joint - Abdullah, Enas Yahya (Current Approaches in Science and Technology Research Vol. 10, 2021)
In this paper general classification of the lubrication regimes in synovial hip joint was given The discussion was focused on two main points, the calculation of film thickness and minimum film thickness for each of the (hydrodynamic lubrication, squeeze film lubrication and, elasto-hydrodynamic lubrication), and the relationship between film thickness and gait cycle (stance phase and swing phase) also and the coefficient friction. Physical properties affecting the film thickness for different types lubrication will be discussed in each lubrication system.